STUDI BIOMETRI BERDASARKAN MERISTIK DAN MORFOMETRIK IKAN GURAMI GALUR BASTAR DAN BLUESAFIR [Biometrical Study Based on Meristic and Morphometric of Giant Gouramy Strain Bastar and Bluesafir] - Radona, Deni; Nafiqoh, Nunak; Arifin, Otong Zenal; Arifin, Otong Zenal (BERITA BIOLOGI, 2017)
Identification of Gouramy is required to obtain phenotype characteristics information of the population for sustainable aquaculture Â practices. In this study phenotype diversity of giant gouramy strain bastar and bluesafir was analyzed based on Â meristic and morphometric measurement. Sample, are taken from 30 individuals of each population. The result showed that there were differences in colour patterns between the two populations, bastar population had yellowish brown body and red fins, whilst bluesafir population had brown blackish brown body and fins. The canonical function of truss morphometric analysis on 21 characteristics showed the measurement distribution of that both populations were in different quadrants. The intrapopulation similarity index showed that population of strain bluesafir had higher genetic similarity (80%) with interpopulation similarity index of 23.3%, while the intrapopulation similarity index of strain bastar was 76.7%.